Efektivitas Komite Audit dan Ukuran Perusahaan: Analisis Corporate Risk Disclosure Perusahaan Sektor Basic Materials di Indonesia - Agati, Allifvia; Sebrina, Nurzi (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to examine the effect of audit committee effectiveness and firm size on the level of Corporate Risk Disclosure (CRD) among basic materials sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2023. Audit committee effectiveness is measured by the number of committee members and the frequency of audit committee meetings, while firm size is proxied by total assets. The study adopts a quantitative approach using panel data regression analysis, with purposive sampling applied to select 50 companies. CRD data were obtained through content analysis of annual reports based on risk classification, using a sentence-level disclosure scoring system across six main risk categories (financial risk, operations risk, empowerment risk, information processing and technology risk, integrity risk, and strategic risk). The results indicate that audit committee size and frequency of audit committee meetings have a significant positive effect on CRD, whereas the firm size does not show a significant influence. These findings support the agency theory by highlighting the important of strong corporate governance structure, particularly effectiveness audit committee and firm size scale to enhanced risk transparency. This study provides important implications for corporate management, investors, and regulators to promoting better risk disclosure practices in the non-financial sector in Indonesia.